1989
DOI: 10.1097/00004032-198911000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Cleanup and Treatment Test at the Nevada Test Site

Abstract: We have conducted experiments to evaluate the effectiveness of removing contaminated soils from the Nevada Test Site with a large truck-mounted vacuum cleaner. Our results show that this method is effective, relatively easy, and safe for equipment operators. With four passes of the truck-mounted vacuum, 92% of the 241Am (and the accompanying 239 + 240Pu) was removed and resuspension rates were reduced by more than 99%. The ecological impact was, however, serious in terms of soil erosion and destruction of smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Similar results were reported by Shinn et al (1989a); a truck mounted vacuum apparatus reduced "'Am in the soil by 92% after four passes. Motor scrapers, like vacuums, actually remove surface soil.…”
Section: E-5supporting
confidence: 87%
See 2 more Smart Citations
“…Similar results were reported by Shinn et al (1989a); a truck mounted vacuum apparatus reduced "'Am in the soil by 92% after four passes. Motor scrapers, like vacuums, actually remove surface soil.…”
Section: E-5supporting
confidence: 87%
“…Brown et al (1988) reported a marked decrease after one year in the effectiveness of removing one centimeter of soil, due largely to downward migration. Shinn et al (1989a) reported that the fractions of %*Am in the top 5 centimeters of plutonium contaminated NTS soils ranged from 62-92%. Howorth and Sandalls (1987) reported on a test of plutonium migration in soil near Seascale in the UK; 90% of the total deposit was found in the top 15 centimeters.…”
Section: E-5mentioning
confidence: 99%
See 1 more Smart Citation
“…In several instances (Shinn et al 1989 , the distributions of suspended mass and suspended activity were very similar. In such cases it is possible to characterize the corresponding distributions by one value of MAD.…”
Section: Particle Size Distribution Of Suspended Particulate Mattermentioning
confidence: 86%
“…Complementary meterological measurements are used (Shinn et al, 1989) to determine relevant weather data at any time during the period of measurement of concentration in air. This is done with an automatic weather station which measures continuously the wind speed, wind direction, and energy budget components of radiant energy.…”
Section: Complementary Meteorological Measurementsmentioning
confidence: 99%